Mesenchymal stem cell-derived exosome-educated macrophages alleviate systemic lupus erythematosus by promoting efferocytosis and recruitment of IL-17+ regulatory T cell - Mingchao Zhang; Takerra K. Johnson-Stephenson; Weiran Wang; Yang Wang; Jing Li; Limin Li; Ke Zen; Xi Chen; Dihan Zhu (Stem Cell Research & Therapy, 2022)
Abstract Background Anti-inflammatory polarized macrophages are reported to alleviate systemic lupus erythematosus (SLE). Our previous studies have demonstrated that exosomes from adipose-derived stem cells promote the anti-inflammatory polarization of macrophages. However, the possible therapeutic effect of exosomes from stem cells on SLE remains unexplored. Methods Exosomes were isolated from the conditioned medium of bone marrow-derived mesenchymal stem cells using ultrafiltration and size-exclusion chromatography and were identified by nanoparticle tracking analysis and immunoblotting of exosomal-specific markers. Macrophages were collected from the MRL/lpr mouse kidney. The phenotype of macrophages was identified by immunoblotting for intracellular markers-inducible nitric oxide synthase (iNOS) and arginase-1 (Arg-1), and flow cytometry for macrophage markers F4/80, CD86, CD206, B7H4, and CD138. Pristane-induced murine lupus nephritis models were employed for in vivo study. Results When macrophages from the kidney of the MRL/lpr mice were treated with exosomes from bone marrow-derived mesenchymal stem cells (BM-MSCs), the upregulation of CD206, B7H4, CD138, Arg-1, CCL20, and anti-inflammatory cytokines was observed, which suggested that the macrophages were polarized to a specific anti-inflammatory phenotype. These anti-inflammatory macrophages produced low levels of reactive oxygen species (ROS) but had a high efferocytosis activity and promoted regulatory T (Treg) cell recruitment. Moreover, exosome injection stimulated the anti-inflammatory polarization of macrophages and increased the production of IL-17+ Treg cells in a pristane-induced murine lupus nephritis model. We observed that exosomes from BMMSCs depleted of microRNA-16 (miR-16) and microRNA-21 (miR-21) failed to downregulate PDCD4 and PTEN in macrophages, respectively, and attenuated exosome-induced anti-inflammatory polarization. Conclusion Our findings provide evidence that exosomes from BMMSCs promote the anti-inflammatory polarization of macrophages. These macrophages alleviate SLE nephritis in lupus mice by consuming apoptotic debris and inducing the recruitment of Treg cells. We identify that exosomal delivery of miR-16 and miR-21 is a significant contributor to the polarization of macrophages. Graphical abstract